DOES SEED HARDNESS BREAKING TECHNIQUES SHOW DIFFERENT EFFECT ON GERMINATION: A TEST OF THREE OKRA VARIETIES? - Babale, Aliyu; Aliyu, Abdullahi M.; Ayuk, Charles N.; Abubakar, Zainab A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
Okra (Abelmoschus esculentus (L) Moench) being among the most important crops grown in northern Nigeria is supposed to be produce in high quantity, but germination of this crop is faced with different challenges due to seed dormancy. This study was conducted in order to compare three techniques employed in breaking seed dormancy of three varieties of A. esculentus. The study was carried out at Botanical Garden, Gombe State University in 2016. Three varieties of A. esculentus namely, Chalawa, Dan Beru and El-Muazu were used. Three treatment techniques employed were seeds soaked in 80% concentrated H2SO4 for three minutes, seeds soaked in 80 C hot water for 12 hours, seeds soaked in water at room temperature for 12 hours and seeds that were not treated (control). Results showed that 80 % concentrated H2SO4 for three minutes was the most effective in breaking of A. esculentus seed dormancy. Although hot water at temperature 80 C for 12 hours decreased percentage of germination than seeds soaked in water at room temperature, this was restricted to Chalawa and Dan Beru varieties. The results of this study suggest that percentage of germination among the three varieties of A. esculentus differs. Therefore, the long period of A. esculentus seed dormancy occurring under natural conditions which is at least ten days; can be shortened to a few days (two days) by subjecting seeds to 80 % concentrated H2SO4 for 3 minutes and water at room temperature for 12 hours particularly for Chalawa and Dan Beru varieties respectively. Our study highlights the need for careful examination of seeds to detect dormancy and the need for proper application of the right treatment for each variety as suggested by the variation in response to treatment by El-Muazu.